2015
DOI: 10.1159/000441362
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and Recurrent Thrombotic Events: Persistence and Portfolio

Abstract: Background: There are very limited prospective data on the significance of persistent antiphospholipid antibodies (aPL) and recurrent thrombo-occlusive events (TOEs). We investigated the prognostic value of (1) 2 newer aPL assays, (2) an aPL portfolio and (3) persistent aPL positivity following stroke. Methods: A total of 1,770 subjects from the APASS-WARSS study underwent further aPL testing for antibodies to phosphatidylserine (aPS) and anti-β2-glycoprotein-I (anti-β2GPI) from stored se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…The primary outcome was a combination of death and major disability (modified Rankin Scale score, [3][4][5][6]. 18 Secondary outcomes were death, major disability, recurrent fatal and nonfatal stroke, and vascular events (eg, vascular deaths, nonfatal stroke, nonfatal myocardial infarction, hospitalized and treated angina, hospitalized and treated congestive heart failure, and hospitalized and treated peripheral arterial disease).…”
Section: Outcome Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was a combination of death and major disability (modified Rankin Scale score, [3][4][5][6]. 18 Secondary outcomes were death, major disability, recurrent fatal and nonfatal stroke, and vascular events (eg, vascular deaths, nonfatal stroke, nonfatal myocardial infarction, hospitalized and treated angina, hospitalized and treated congestive heart failure, and hospitalized and treated peripheral arterial disease).…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…3 Anticardiolipin antibodies (aCL) and lupus anticoagulant antibodies were the most frequently studied members and had been associated with an increased risk of recurrent thrombo-occlusive events and death after stroke in some but not in all studies. [4][5][6][7][8] Recently, studies suggest that antibodies directed against phosphatidylserine (antiphosphatidylserine antibodies [aPS]) may be a useful marker for the syndrome. [9][10][11][12] Population-based studies showed an independent association of aPS with ischemic stroke.…”
mentioning
confidence: 99%
“…However, APS is a heterogeneous disease and the clinical relevance of the aPL profile, in particular TP, in the clinical course of PAPS has not yet been confirmed . A recent meta‐analysis demonstrated that each aPL (LAC, aCL, and aB2GP1) were independently associated with increased risk of thrombosis in PAPS, particularly LAC was associated with the highest risk .…”
Section: Introductionmentioning
confidence: 99%
“…Ten‐year survival probability was 90.7% . Persistence of aPL positivity in patients with previous cerebrovascular events increases the risk of recurrence, whereas persistent anti‐b2GPI are associated with decreased time to thrombotic events and death . Interestingly, an association between patent foramen ovale with atrial septal aneurysm and APS has been reported, raising further risk of ischemic stroke …”
Section: Causes Of Recurrent Multi‐territory Embolic Cerebral Infarctionmentioning
confidence: 99%
“…45 Persistence of aPL positivity in patients with previous cerebrovascular events increases the risk of recurrence, whereas persistent anti-b2GPI are associated with decreased time to thrombotic events and death. 46,47 Interestingly, an association between patent foramen ovale with atrial septal aneurysm and APS has been reported, raising further risk of ischemic stroke. 48 Even despite anticoagulation treatment, individuals with APS carry a substantial risk of future ischemic stroke, especially when positivity for IgM-type anti-B2GPI is persistent.…”
Section: Causes Of Recurrent Multi-territory Embolic Cerebral Infarctmentioning
confidence: 99%